Uganda Economic Update, January 2017 : Step by Step - Let’s Solve the Finance Puzzle to Accelerate Growth and Shared Prosperity - World Bank (World Bank, Washington, DC, 2017)
The negative GDP growth rate recorded in the first quarter of FY 2016/17 is indicative of the recent difficulties that Uganda has faced in achieving the rates of growth required to enable the country to fulfill its aspirations. In the period from the 1990s to 2010, Uganda achieved average annual rates of economic growth of around seven percent, far higher than many peers. The sustained growth was the result of macroeconomic stability, post-conflict rebound, and market and institutional reforms which transformed Uganda from a failed state to one of the fastest growing economies in the world. However, the average annual growth in the five-year period to FY 2015/16 has decelerated to 4.5 percent. In sharp contrast to the earlier period, this is significantly lower than the average rate recorded by low income countries in the same period. The decline since 2011 is partly related to the increasingly volatile external environment and partly to domestic policy slippages. Policy frameworks held up well during the 2016 election cycle, but serious strains related to the impact of the drought on agriculture and of the civil strife in South Sudan are now materializing. It is important to ensure that the fiscal impact of these shocks does not transmit into macro policy slippages, with past experiences showing how damaging such slippagescan be to growth. In order to return to the levels of economic growth recorded in the immediate post-reform era, it is vitally necessary to address binding constraints and to transform the economy to facilitate the achievement of higher levels of productivity through diversification into a more resilient range of economic activities. As with previous editions of this update, the eighth Uganda Economic Update provides an analysis of the current state of the economy, while also focusing on a particular subject of significance. In this update, the focus is on the state ofthe financial system, with an analysis of the means by which this system can be leveraged to accelerate growth and development through higher levels of financial inclusion. A well-functioning financial sector enables financial institutions to provide affordable credit and other financial services to a greater proportion of the population. This encourages the emergence of new businesses and facilitates the growth of existing businesses. At the household level, it enables tosmooth the patterns of consumption, to invest in human capital development, and to accumulate physical and other assets. Together or individually, all of these outcomes play a significant role in the achievement of higher levels of economic growth and shared prosperity.